Comparative genome analysis of Alkhumra hemorrhagic fever virus with Kyasanur forest disease and tick-borne encephalitis viruses by the in silico approach - Palanisamy, Navaneethan; Akaberi, Dario; Lennerstrand, Johan; Lundkvist, Åke (Pathogens and global health, 2018)
Alkhumra hemorrhagic fever virus (AHFV), a relatively new member of the Flaviviruses, was discovered in Saudi Arabia 23 years ago. AHFV is classified in the tick-borne encephalitis virus serocomplex, along with the Kyasanur forest disease virus (KFDV) and tick-borne encephalitis virus (TBEV). Currently, very little is known about the pathologies of AHFV. In this study, using the available genome information of AHFV, KFDV and TBEV, we have predicted and compared the following aspects of these viruses: evolution, nucleotide and protein compositions, recombination, codon frequency, substitution rate, N- and O-glycosylation sites, signal peptide and cleavage site, transmembrane region, secondary structure of 5’ and 3’ UTRs and RNA-RNA interactions. Additionally, we have modeled the 3D protease and RNA-dependent RNA polymerase structures for AHFV, KFDV and TBEV. Recombination analysis showed no evidence of recombination in the AHFV genome with that of either KFDV or TBEV, although single break point analysis showed that nucleotide position 7399 (in the NS4B) is a breakpoint location. AHFV, KFDV and TBEV are very similar in terms of codon frequency, the number of transmembrane regions, properties of the polyprotein, RNA-RNA interaction sequences, NS3 protease and NS5 polymerase structures and 5’ UTR structure. Using genome sequences, we showed the similarities between these closely- related viruses on several different areas.